Electron impact excitation of the Tl+ ion: resonance and cascade transitions. (17th August 2022) - Roman, Viktoria; Gomonai, Aleksandr I; Sharma, Lalita; Sahoo, Aloka Kuma; Gomonai, Anna N
Abstract: Results of experimental and theoretical investigations into the electron-impact excitation of the resonance 6 s 6 p 1 P 1 ° → 6 s 2 1 S 0 (132.2 nm), as well as the cascade 6 s 7 s 1 S 0 → 6 s 6 p 1 P 1 ° (309.2 nm) and 6 p 2 1 D 2 → 6 s 6 p 1 P 1 ° (150.8 nm) spectral transitions from the ground 6 s 2 1 S 0 level in the thallium ion, are presented. Crossed beams of electrons and Tl + ions in combination with a spectroscopic method were used in the experiment. Measured cross sections have a distinct resonance structure arising mainly from the electron decay of atomic 5 d 9 6 s 2 6 p 2, 5 d 10 6 s 7 s ( 1 S ) np ( n ⩾ 7), 5 d 10 6 s 6 d ( 1 D ) np ( n ⩾ 6), 5 d 10 6 s 6 d ( 1 D ) nd ( n ⩾ 6) and ionic 5 d 9 6 s 2 np, 5 d 9 6 s 2 nd, 5 d 9 6 snp ( n ⩾ 6) autoionizing levels, as well as radiative transitions from the higher 6 s 7 s 1 S 0, 6 s 6 d 1 D 2, and 6 p 2 1 D 2, 1 S 0 ionic levels. Relativistic distorted wave (RDW) calculations are performed to obtain the effective cross sections for the above transitions. The absolute values of the cross sections are found to be 1.39 × 10 −16 cm 2 at 300 eV for the λ 132.2 nm resonance line, and 0.11 × 10 −16 cm 2 and 0.56 × 10 −16 cm 2 at 100 eV for the λ 309.2 nm and λ 150.8 nm lines, respectively. The contribution of the cascade transitions being studied to the effective cross section of the λ 132.2 nm resonance line at the energy of 100 eV is about 30%. A calculation using the semi-empirical Van Regemorter formula is also performed to obtain the effective cross section of the resonance λ 132.2 nm line. The absolute value of the cross section at 300 eV is found to be nearly the same as that given by the RDW calculation.